Anatomical Step-by-Step Dissection of Complex Skull Base Approaches for Trainees: Surgical Anatomy of the Bifrontal Transbasal Approach, Surgical Principles, and Illustrative Cases - Vilany, Larissa; Dang, Danielle D.; Agosti, Edoardo; Plou, Pedro; Leonel, Luciano C. P. C.; Graepel, Stephen; Pinheiro-Neto, Carlos D.; Lanzino, Giuseppe; Link, Michael J.; Peris-Celda, Maria (Journal of Neurological Surgery Part B: Skull Base, 2023)
Introduction The transbasal approach traditionally uses a bicoronal scalp incision with bifrontal craniotomy to establish an extradural midline skull base working corridor. Depending on additional craniofacial osteotomies, this approach can expand its reach to the nasal cavity and paranasal sinuses and may be employed for the resection of particularly complex sinonasal and midline skull base tumors. Given its discrepancy in nomenclature and differences in interoperator technique, we propose a practical, operatively oriented guide for trainees performing this approach.Methods Three formalin-fixed, latex-injected specimens were dissected under microscopic magnification and endoscopic-assisted visualization. Stepwise dissections of the transcranial-transbasal approach with common modifications were performed, documented with three-dimensional photography, and supplemented with representative case applications.Results The traditional transbasal approach via bifrontal craniotomy affords wide extradural access to the anterior cranial fossa and central skull base. The addition of craniofacial osteotomies further expands access into the sinonasal cavities, clivus, and craniocervical junction. Key steps described include patient positioning, bicoronal skin incision, pericranial graft harvest, bifrontal craniotomy, orbital rim osteotomy, sphenoidotomy, bilateral ethmoidectomies, and microsurgical dissection of the sellar region. Basal superior sagittal sinus ligation and durotomy allow for intradural exposure. Reconstruction techniques are also discussed.Conclusion While the transbasal approach is rich with historical descriptions, illustrations, and modifications, its stepwise performance may be relatively unknown and unclear to younger generations of trainees. We present a comprehensive guide to optimize familiarity with the transbasal approach and its indications in the surgical anatomy laboratory, mastery of the relevant microsurgical anatomy, and simultaneous preparation for learning and participation in the operating room.
Keywords: transbasal; bifrontal; central skull base; anterior cranial fossa; tumor; step-by-step; trainee